The Influence of Earnings Management on the Value Relevance of Accounting Information - Rahmah, Rahmah; Rezki Akbar Norrahman (Journal of Scientific Interdisciplinary, 2024)
This research aims to investigate the influence of earnings management practices on the value relevance of accounting information in the Indonesian business environment. The research method used is qualitative with a library study approach and document content analysis. Data was obtained through in-depth interviews with related parties such as auditors and financial managers, as well as analysis of the contents of documents in the form of financial reports and company meeting notes. The research results show that earnings management practices can reduce the value relevance of accounting information by affecting the quality of information conveyed in financial reports. Practices such as increasing revenue estimates or delaying expense recognition can cloud the picture of a company's true performance, which in turn affects economic decision making. These findings emphasize the importance of transparency and integrity in accounting practices to maintain the value relevance of accounting information for stakeholders. The implication of this research for accounting theory is the need to pay attention to earnings management practices within a broader theoretical framework regarding the integrity of accounting information. From a practical perspective, companies need to increase awareness of the importance of honest accounting practices and comply with applicable standards to minimize unethical earnings management practices. This implication is also relevant for regulators in strengthening regulations related to financial reporting in order to maintain the integrity of the capital market in Indonesia.